1978
DOI: 10.1111/j.1095-8649.1978.tb04192.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of season, thermal loading and red‐sore disease with various haematological parameters in Micropterus salmoides

Abstract: One hundred and fifty largemouth bass (Micropterus salmoides) were caught during the mid-winter and mid-summer months in Par Pond, an 1120 ha cooling reservoir located on Savannah River Plant near Aiken, SC. Equal numbers of fish were taken from ambient and thermally altered (> 10" C ambient) areas of the lake. The total length and weight of each bass was noted, along with the presence or absence of lesions associated with red-sore disease (caused by the bacterium, Aeromonas hydrophila and the ciliate, Epistyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Although seasonal changes in thyroid hormones are common in fish (Leatherland 1982), there is limited published information on plasma thyroid hormones in these two species. Hazen et al (1978) observed higher levels of plasma T 4 in summer compared to winter in a reservoir population of largemouth bass. Spring increases in both plasma T 4 and T 3 were observed in feral populations of brown bullhead (Burke and Leatherland 1983).…”
Section: Discussionmentioning
confidence: 79%
“…Although seasonal changes in thyroid hormones are common in fish (Leatherland 1982), there is limited published information on plasma thyroid hormones in these two species. Hazen et al (1978) observed higher levels of plasma T 4 in summer compared to winter in a reservoir population of largemouth bass. Spring increases in both plasma T 4 and T 3 were observed in feral populations of brown bullhead (Burke and Leatherland 1983).…”
Section: Discussionmentioning
confidence: 79%
“…Severe haemorrhagic necrosis of gill lamellae and filaments; haemorrhagic necrosis and inflammation of underlying supporting tissues (x35). Rased on the infection scheme proposed hy , and on ohservations generated in the present study, we believe that the pathobiology of red-sore disease among largemouth bass in Par Pond follows a clear pattern: namely, elevated water temperature stimulates increased metabolism of bass, resulting in increased catabolism of stored fat and protein; body conditions of these bass then decline according to the duration and magnitude of exposure to elevated temperature Hazen, Esch, Glassman & Gibbons, 1978). Increased temperatures either directly, or indirectly for bass with lowered body conditions, cause increased production and release of ACTH which, in turn, stimulates production and release of corticosteroids, primarily cortisol.…”
Section: Discussionmentioning
confidence: 89%
“…Recent studies have shown that the incidence of redsore disease is significantly higher among fish in thermally altered parts of a South Carolina reservoir that receives heated effluent from a nuclear production reactor (4). The positive correlation between red-sore disease and thermal effluent was related to thermal stress on potential fish hosts (3,7). A more recent study demonstrated a significant positive correlation between densities of A. hydrophila in the water column and the incidence of red-sore disease in the fish population over a 3-year period (T; C. Hazen, Ph.D. thesis, Wake Forest University, Winston-Salem, N.C., 1978).…”
mentioning
confidence: 99%